Modified band alignment effect in ZnO/Cu2O heterojunction solar cells via Cs2O buffer insertion - Eom, Kiryung; Lee, Dongyoon; Kim, Seunghwan; Seo, Hyungtak (Journal of Physics D: Applied Physics, 2018)
The effects of a complex buffer layer of cesium oxide (Cs2O) on the photocurrent response in oxide heterojunction solar cells (HSCs) were investigated. A p-n junction oxide HSC was fabricated using p-type copper (I) oxide (Cu2O) and n-type zinc oxide (ZnO); the buffer layer was inserted between the Cu2O and fluorine-doped tin oxide (FTO). Ultraviolet-visible (UV-vis) and x-ray and ultraviolet photoelectron spectroscopy analyses were performed to characterize the electronic band structures of cells, both with and without this buffer layer. In conjunction with the measured band electronic structures, the significantly improved visible-range photocurrent spectra of the buffer-inserted HSC were analyzed in-depth. As a result, the 1 sun power conversion efficiency was increased by about three times by the insertion of buffer layer. The physicochemical origin of the photocurrent enhancement was mainly ascribed to the increased photocarrier density in the buffer layer and modified valence band offset to promote the effective hole transfer at the interface to FTO on the band-alignment model.
Keywords: Band alignments; Cs2O buffer; Cu2O; Electronic band structure; Fluorine doped tin oxide; Heterojunction solar cells; Photocurrent enhancement; Power conversion efficiencies; band alignment; Cs2O buffer; Cu2O; solar cells; ZnO